SMART-БИОСОРБЕНТЫ НА ОСНОВЕ ПИВОВАРЕННЫХ ДРОЖЖЕЙ И НАНОСТРУКТУРИРОВАННОГО МАГНЕТИТА - Аронбаев, Сергей; Аронбаев , Дмитрий (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The possibility and options of using a magnetically controlled sorbent based on the cell walls of brewing еast and nanostructured magnetite in biosorption technologies for remediation of wastewater and surface waters are shown.